Map of spinal neurons activated by chemical stimulation in the nucleus raphe magnus of the unanesthetized rat - Bett, Kerstin; Sandkühler, Jürgen (Neuroscience, 1995)
The expression of the proto-oncogene c-fos was used as a cellular marker of spinal cord neurons activated by microinjection of kainic acid into the medullary nucleus raphe magnus of awake and drug-free Sprague-Dawley rats. The c-FOS protein was detected by immunocytochemistry. We found increased immunoreactivity bilaterally in laminae I-VI of the dorsal horn. The strongest c-FOS expression was observed within the inner layer of lamina II near its border with lamina III. In the ventral horn no c-FOS immunoreactivity was observed. Thus, the present results provide evidence for a descending excitation of neurons predominantly in inner lamina II, possibly mediating nucleus raphe magnus-induced inhibition of neurons in other laminae.